Modern child psychology - Chand, Tara (India, 2006)
In the beginning of the twentieth century various theories about the nature of the learner had been advanced by many psychologists. Thorndike' theory about child nature was the most prominent, which became the bedrock of child psychology. After this various other theories also laid stress on the fact that the understanding about the learner's disposition was necessary for any educational programme.
Keywords: Child development; Child psychology